The impact of synchronous collaborative writing and Google Docs collaborative features on enhancing students’ individual writing performance - Husam Masaoud Alwahoub; Nayef Jomaa Jomaa; Mohd Nazri Latiff Azmi (Indonesian Journal of Applied Linguistics, 2022)
Collaborative writing has gained researchers’ attention due to its efficiency in enhancing students’ writing abilities compared to traditional writing. More recently, more emphasis has been on computer-based versions of collaborative writing because of the introduction of Web 2.0 and other cloud-based writing tools, such as Google Docs and Wikis, especially at the tertiary level. However, there is still a dearth of research regarding synchronous collaborative writing in mainstream K-12 classes. Therefore, this quasi-experimental quantitative study aims at investigating the impact of synchronous collaborative writing on developing fourth-grade EFL students’ writing. The data were collected from the pre-tests and the post-tests of 49 students in a technology-supportive K-12 school in Riyadh-Saudi Arabia and were analyzed using independent samples t-test via SPSS version 23. The analysis of individual writing performance in the pre- and post- tests revealed that the total mean scores of the Content, Language use, and Organisation measurements have increased in both the experimental group, after experiencing collaborative writing using Google Docs, and the control group, who used traditional pen-and-paper writing. In addition, significant differences existed in the three writing tasks (Narrative, Argumentative, and Informative) in the post-test scores of the experimental group as well as in the post-test scores between the groups, with the experimental group scoring higher than the traditional writing group. However, no significant difference was revealed between the pre- and post- test scores of the control group. In addition, it was found that the task type variable plays a vital role in collaborative writing. These findings are significant for both educators and students in implementing computer-based collaborative writing in mainstream classes and for researchers who are interested in web-based education and E-learning.